Pengaruh Kualitas Produk, Kualitas Pelayanan dan Kepercayaan Konsumen Terhadap Minat Beli Produk CV. Fanjaya Logam di Kabupaten Kendal - Hidayatullah, Muhammad Syarif; Huda, Haris Ihsanil; Siswanto, Edy (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of product quality, service quality, and consumer trust on purchase intention among customers of CV. Fanjaya Logam. The research employed a quantitative approach using questionnaires distributed to 71 respondents, and the data were analyzed with IBM SPSS Statistics software. The validity test results indicated that all questionnaire items were valid, with correlation values exceeding the r-table value of 0.234. The reliability test showed a Cronbach’s Alpha coefficient of 0.698 (>0.60), confirming the reliability of the instruments. Classical assumption tests, including multicollinearity, heteroscedasticity, and normality, confirmed that the regression model was appropriate for use. The multiple linear regression analysis revealed that only consumer trust had a positive and significant effect on purchase intention (t = 3.704; sig. < 0.001), whereas product quality and service quality showed no significant effects. Simultaneously, all three independent variables significantly influenced purchase intention, as indicated by the F-value of 5.206 > 3.980 and an Adjusted R² of 0.153.